A argumentação e a experimentação investigativa no ensino de matemática: o problema das formas em um clube de ciências - ALMEIDA, Willa Nayana Corrêa (Universidade Federal do Pará, 2019)
The present study objective to analyze the contributions of the interventions of the teacher-monitor for the emergence and development of the argumentation among students participating in the Science Club "Prof. Dr. Cristovam W. P. Diniz", of the Federal University of Pará - Campus Castanhal, during an investigative experimental activity on the introductory concepts of area and perimeter. It Emerged from the reflections of the researcher during her personal and professional experiences in the classroom, and that contribute to the constitution of our identity as educator of Mathematics. In view of this, we apply a sequence of teaching based on the stages of investigative experimentation, in which we seek to identify, in our interventions as teacher-monitors, the pedagogical and epistemological purposes expressed to favor the argumentation among the students. Regarding the students' statements, we tried to verify in the argumentative process developed, both the elements and the structure according to the of Toulmin’s Pattern (2001), such as the epistemological operations presented by students expressing the relations that occurred during the construction of mathematical knowledge. The research is characterized as qualitative, in which we use as video recording instruments, video recordings, photographs, audio recordings and field notes, with subsequent transcription of the subjects' speeches. For the interpretation of the information collected, we chose to use Content Analysis. The space investigated is considered an alternative environment destined for teaching, research and extension of didactic actions turned to Science and Mathematics. The participants were four students of the fifth year and three of the sixth year, totalizing seven subjects. During the analysis, it was possible to identify, in each of the episodes considered more prominent, that our interventions as teacher-monitor had great relevance, since from the developed epistemological purposes and pedagogical actions it was possible organize and guide the investigative activity so that it helps in the emergence of argumentation and the construction of mathematical knowledge. We verified that emerged argumentative organisms according to the Toulmin pattern, being constituted of data (D), conclusion (C), warranty (W), backing (B), modal qualifier (Q) and refutation (R). In relation to the epistemological operations presented by the students in the development of the argumentation, we perceive that various forms of action and thought have arisen, being mainly explored deduction, induction, causality, definition, classifying, appeal to analogies and attributes, consistency with experience and plausibility. The final product generated by the research consists of a video guidance that explains the stages of investigative experimentation and evidences the attitude of the educator for the emergence and development of argumentation among students.